Quality of life of institutionalized elderly in an urban area of North Kerala, India - Sanya, Rameela; Kumaran, Jayasree Anandabhavan (International Journal Of Community Medicine And Public Health, 2020)
Background: Being transferred from home to nursing care facility is great challenge for elderly as they have to face a radical change in their lifestyle. However, not much is known about the response of its residents to institutionalization and its impact on their physical and mental health. Objective is to assess quality of life (QOL) of institutionalized elderly in an urban area of North Kerala and its association with sociodemographic factors. Methods: A cross- sectional study was conducted among 202 elderly residing in old age homes (OAH). Data was collected using WHO QOL BREF. Data analysed using SPSS version 16.0. Results expressed terms of mean, SD, frequencies, percentages. Kruskal Wallis and Mann Whitney U test used to find association between domain-wise (physical, psychological, social relationships, environmental) QOL and sociodemographic factors. Results: Out of 202 elderly residing in OAH, majority were females (60.4%), belonged to 60-69 years age-group (39.6%), Hindus (59.9%) and widowed (49.5%). Majority had ‘moderately poor QOL in all domains, except environmental domain where majority had ‘moderately good’ QOL. Highest mean scores were found in environmental domain. Statistically significant association was found between physical domain and age- groups, gender, marital and educational status; and between psychological domain and gender, current occupational status. Environmental domain was associated with age-groups, religion, financial dependency, current occupational status. Conclusions: Elderly belonging to younger age- group (60-69 years), male gender, educated, retired group and those without morbidity had better QOL.